A comparison of farming practices and performance for wheat production in Haryana, India. (July 2015) - Coventry, D.R.; Poswal, R.S.; Yadav, Ashok; Riar, Amritbir Singh; Zhou, Yi; Kumar, Anuj; Chand, Ramesh; Chhokar, R.S.; Sharma, R.K.; Yadav, V.K.; Gupta, R.K.; Mehta, Anil; et al.
Highlights: The survey of agronomic inputs and output in wheat production was conducted in Haryana (India). Agronomic inputs and yield data are analysed by regression tree and technical efficiency (TE). Zero tillage and targeted use of micronutrients, plus use of macro-nutrients can enhance wheat production and productivity. There was an overall higher level of TE in rice–wheat rotation. Managements including early sowing, optimal N fertilizer rate, and reduced tillage can contribute to yield increase. Abstract: An extensive stratified survey was conducted in two different wheat growing seasons in all districts of Haryana (India) to evaluate current agronomic practices and assess performance in wheat production with the purpose of identifying where farmers can make further changes in practices. The survey involved 116 villages (927 farmers) in 2008 and 103 villages (823 farmers) in 2010. Different sized farming operations from each village were surveyed to represent all socio-economic categories of farmers. Agronomic inputs (tillage method, fertilizer practice, variety choice, time of sowing, irrigation, and rotation practice) and yield data are presented as mean data, and individual farmer's information is represented by regression tree (RT) analysis to highlight primary associations between cropping management and wheat yield and the technical efficiency (TE) measure. TE was calculated using the key agronomic variables obtained from the survey, and the farms with the highest TE values were assessed as having the superior 'best practice' technology. In the districts where the rice–wheat rotation was adopted, there was an overall higher level of TE. Where rice–wheat rotation is the main cropping practice (for example in Kaithal and Kurukshetra), many of the farmers have adopted zero tillage farming methods, with one third of farmers in Kaithal using zero tillage for planting wheat. In contrast, in Sirsa district where cotton was favoured by the farmers as their monsoon season crop, there were no farms where zero tillage was practised. Also, there was also no zero tillage farming where the pearl millet/cluster bean rotation was used as the monsoon season crop. In most cases farmers use a two applications of nitrogen fertilizer applied post-emergence, particularly in the rice–wheat and cotton–wheat districts. The survey also showed that application of potassium fertilizer and use of zinc is regionally specific and this is consistent with the soil maps that show the potential for deficiency of these nutrients in Haryana districts. Sowing in the rice–wheat districts was mostly at the recommended time in early November. The highest number of irrigations occurred in the districts using the pearl millet–wheat and cluster bean–wheat rotations where sprinkler irrigation is the main application practice. The analysis of TE provides a useful comparison when the 5 different farm size categories are separated. There was no difference in TE with farm size, suggesting the message concerning best practice for wheat production is available to and adopted by farmers irrespective of scale of operation. This analysis highlights where extension messages could be focused, whether for zero tillage in the non-rice districts, management of macro-nutrients, or the targeted use of micronutrients.